2017
DOI: 10.37393/jass.2017.02.4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Anxiety and Perceived Stress Among the Participants in the XXV Antarctic Expedition

Abstract: The ХХV Bulgarian Antarctic expedition on the Livingston isles, which included scientists and alpinists, began in November 2016. The participants' activities are highly dependent on the extreme conditions they are in.The aim of the present researchis to studydynamics ofanxiety and perceived stress and to find a relation with the participants'preferred strategies for coping with stress in highly risky activities in an extreme climatic and social environment.Subject of the study were 21 participants in the ХХV B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Just as physical activity can improve mood, other coping activities might also reduce negative mood during a period of recovery or stress, such as leissure activities, social networking, artistic activities or learning activities (Waters and Moore, 2002 ; Drake et al, 2014 ; Domuschieva-Rogleva and Iancheva, 2017 ; Chan et al, 2019 ). It has been discussed whether the practice of these activities' directly influences mood states, or whether such influence is mediated via the reduction of stressful thoughts and the increase in motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Just as physical activity can improve mood, other coping activities might also reduce negative mood during a period of recovery or stress, such as leissure activities, social networking, artistic activities or learning activities (Waters and Moore, 2002 ; Drake et al, 2014 ; Domuschieva-Rogleva and Iancheva, 2017 ; Chan et al, 2019 ). It has been discussed whether the practice of these activities' directly influences mood states, or whether such influence is mediated via the reduction of stressful thoughts and the increase in motivation.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Bulgarian scientists found that participants' perceived stress levels at the beginning of an Antarctic expedition were significantly higher compared to the results at the end of the expedition. A high level of perceived stress has the greatest impact on anxiety levels in study participants [15]. In another study, the dynamics of stress and recovery reactions and their relationship with the perception of environmental development during one year of polar wintering of expedition members in various environmental conditions of the subantarctic and Antarctic polar stations was studied.…”
Section: Introductionmentioning
confidence: 99%
“…The features of adaptation to the extreme natural and climatic conditions of the Arctic can be observed when studying the dynamics of the state of participants in scientific expeditions. A study by Bulgarian scientists found that participants’ perceived stress levels at the beginning of an Antarctic expedition were significantly higher compared to the results at the end of the expedition [ 15 ]. A high level of perceived stress has the greatest impact on anxiety levels in study participants [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Bulgarian scientists found that participants’ perceived stress levels at the beginning of an Antarctic expedition were significantly higher compared to the results at the end of the expedition [ 15 ]. A high level of perceived stress has the greatest impact on anxiety levels in study participants [ 15 ]. The dynamics of stress and recovery reactions and their relationship with the perception of environmental development during one year of polar wintering of expedition members in various environmental conditions of the subantarctic and Antarctic polar stations was studied by the international scientific team [ 16 ].…”
Section: Introductionmentioning
confidence: 99%